Deep submicrometer YAG:Ce phosphor particles with high photoluminescent quantum yield prepared by flame spray synthesis. Issue 8 (28th April 2017) - Borlaf, Mario; Kubrin, Roman; Aseev, Vladimir; Petrov, Alexander Yu; Nikonorov, Nikolay; Graule, Thomas
Abstract: YAG:Ce materials have been extensively studied as phosphors for blue to white light conversion. In the last years, the preparation methods of YAG:Ce powders in the nanometric scale have received intensive attention due to their special optical properties. In this context, the preparation of luminescent particles with high quantum yield (QY) and particle size in the deep submicrometer range is the main focus of this work. Amorphous and hexagonal YAG:Ce nanoparticles (<20 nm) with the stoichiometric composition of YAG:Ce were synthesized by liquid‐feed flame spray synthesis. The crystal phase, particle size, and specific surface area (SSA) evolution with the calcination temperature were investigated. A direct conversion from the amorphous/hexagonal phase to the cubic one was observed at T ≥900°C, together with an increase in the particle size into the range 100‐350 nm and a corresponding decrease in the SSA. Zeta potential of the particles in aqueous dispersions and their photoluminescent properties were characterized. The QY increased for the phosphor powders with lower Ce 3+ concentration. The highest QY of 70%‐72% was obtained for powders containing cerium doping of 0.1 mol% and spanning the size range between 130 and 270 nm.